The parasite Ichthyophonus sp. in Pacific herring from the coastal NE Pacific. Issue 4 (31st March 2015) - Hershberger, P K; Gregg, J L; Hart, L M; Moffitt, S; Brenner, R; Stick, K; Coonradt, E; Otis, E O; Vollenweider, J J; Garver, K A; Lovy, J; Meyers, T R
Abstract: The protistan parasite Ichthyophonus occurred in populations of Pacific herring Clupea pallasii Valenciennes throughout coastal areas of the NE Pacific, ranging from Puget Sound, WA north to the Gulf of Alaska, AK. Infection prevalence in local Pacific herring stocks varied seasonally and annually, and a general pattern of increasing prevalence with host size and/or age persisted throughout the NE Pacific. An exception to this zoographic pattern occurred among a group of juvenile, age 1+ year Pacific herring from Cordova Harbor, AK in June 2010, which demonstrated an unusually high infection prevalence of 35%. Reasons for this anomaly were hypothesized to involve anthropogenic influences that resulted in locally elevated infection pressures. Interannual declines in infection prevalence from some populations (e.g. Lower Cook Inlet, AK; from 20–32% in 2007 to 0–3% during 2009–13) or from the largest size cohorts of other populations (e.g. Sitka Sound, AK; from 62.5% in 2007 to 19.6% in 2013) were likely a reflection of selective mortality among the infected cohorts. All available information for Ichthyophonus in the NE Pacific, including broad geographic range, low host specificity and presence in archived Pacific herring tissue samples dating to the 1980s, indicate a long‐standing host–pathogen relationship.